India's Aadhaar project: the unprecedented and unique partnership for inclusion / Roger J. Chin, Gregory Hennessy and Toby Madubuko - Roger, J. Chin; Gregory, Hennessy; Toby, Madubuko (Faculty of Administrative Science and Policy Studies, 2015)
The burgeoning economy of India still precludes many marginalized individuals at the bottom of the pyramid from obtaining basic benefits and welfare services due to the lack of a proper form of identification. The Unique Identification Authority of India (UIDAI) established a program in 2009 called Aadhaar as a method for providing identification to the marginalized residents of India. The purpose of the identification project was to promote greater social and financial inclusion for all residents in the formal economy of India. UIDAI leadership implemented a public-private partnership that leveraged the strengths of both the Government of India and the private sector, giving Aadhaar the ability to overcome the challenges of a project with such a large scope and size. This comprehensive analysis may provide a broader interest for developing or industrial countries with a model for implementing their own mechanism for the provision of a nationally recognized identification system.